Leukocyte-specific protein 1 is associated with the stage and tumor immune infiltration of cervical cancer - Dianqin Xu; Xinzhu Zhou; Shaoju Min; Yu Zhang; Xiaoyu Zhu; Kun Qiao; Luhong Xie; Ji Ren; Yameng Liu; Ziwen Xiao; Yujie Tan (Scientific Reports)
Abstract Cervical cancer (CC) is a leading cause of cancer-related mortality among women and is strongly associated with persistent infection by high-risk human papillomavirus (HR-HPV), particularly the HPV16 subtype. Existing detection methods have limitations in meeting clinical requirements. This study aims to identify biomarkers that can aid in the staging and prognosis of cervical cancer. Cervical epithelial exfoliated cell samples were collected from three groups: HPV16-negative normal cervix, HPV16-positive normal cervix, and HPV16-positive cervical cancer. Differential expression proteins (DEPs) were identified using TMT-LC–MS/MS technology, and their associations with tumor-infiltrating lymphocytes (TILs) and immune regulatory molecules were analyzed. Leukocyte-specific protein 1 (LSP1), an intracellular F-actin-binding protein predominantly expressed in macrophages, neutrophils, B cells, and T cells, was identified as a potential biomarker. The expression levels of LSP1 were evaluated and validated using the Human Protein Atlas (HPA) database, immunohistochemistry (IHC), Western blotting (WB), and real-time quantitative PCR (RT-qPCR). Multiplex fluorescence immunohistochemistry (mIHC) was employed to assess the co-localization of LSP1 with CD4+ and CD8+ T cells. Results indicated that both protein and mRNA levels of LSP1 were significantly elevated in cervical cancer tissues compared to adjacent non-tumor tissues. Notably, LSP1 expression was higher in early-stage cervical cancer (Stage IB) than in advanced-stage disease (Stage IIIC). Furthermore, LSP1 was predominantly localized in CD4+ and CD8+ T cells with low TIM-3 expression. Analysis of public databases (GEPIA, TIMER2.0, and TISIDB) revealed that higher LSP1 mRNA levels correlated with better patient outcomes. LSP1 expression was positively associated with the abundance of major TILs and immune regulatory molecules, particularly activated B cells, CD8+ T cells, and CD4+ T cells, while negatively correlated with M2 macrophages and myeloid-derived suppressor cells. These findings indicate that the expression levels of LSP1 in cervical tissues are correlated with cancer staging and patient prognosis, potentially reflecting both tumor immune infiltration and T-cell exhaustion within the tumor microenvironment (TME).